Potentials of Endothelial Colony-Forming Cells: Applications in Hemostasis and Thrombosis Disorders, from Unveiling Disease Pathophysiology to Cell Therapy - Schwarz, Nadine; Yadegari, Hamideh (Hämostaseologie, 2023)
Endothelial colony-forming cells (ECFCs) are endothelial progenitor cells circulating in a limited number in peripheral blood. They can give rise to mature endothelial cells (ECs) and, with intrinsically high proliferative potency, contribute to forming new blood vessels and restoring the damaged endothelium in vivo. ECFCs can be isolated from peripheral blood or umbilical cord and cultured to generate large amounts of autologous ECs in vitro. Upon differentiation in culture, ECFCs are excellent surrogates for mature ECs showing the same phenotypic, genotypic, and functional features. In the last two decades, the ECFCs from various vascular disease patients have been widely used to study the diseases' pathophysiology ex vivo and develop cell-based therapeutic approaches, including vascular regenerative therapy, tissue engineering, and gene therapy. In the current review, we will provide an updated overview of past studies, which have used ECFCs to elucidate the molecular mechanisms underlying the pathogenesis of hemostatic disorders in basic research. Additionally, we summarize preceding studies demonstrating the utility of ECFCs as cellular tools for diagnostic or therapeutic clinical applications in thrombosis and hemostasis.
Keywords: endothelial cells; endothelial colony-forming cells; ex vivo model; von Willebrand disease; thrombosis